Developers in focus! Developer Experience Analysis in a Collaborative Modeling Tool - Silva, Miguel; Teixeira, Lígia; Silva, Afonso; Gomes, Genildo; Barreto, Leonardo; Gadelha, Bruno; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Developer Experience (DX) is defined concerning how developers think, feel and value their work. Considering that developers’ satisfaction and feelings impact the productivity and success of projects, it is necessary to understand how to improve their experience throughout the stages of the development process. Within this context, we investigated the developer experience and the main factors that affect using a collaborative UML diagram modeling tool. For this, we use three techniques as evaluation methods: the DEXI scale, the Intrinsic Motivation Inventory, and Focus Group. We executed an empirical study with 20 people learning to use a modeling tool. Qualitative results highlight that the organization of user interface components and specific support aspects for collaborative work affected DX at different levels. Other essential elements, such as ease of use, rework, and organization, were also identified. The results aim to improve developers’ experience in software modeling tools, making the experience satisfactory and pleasant.